ANALISIS PENGELOLAAN REKAM MEDIS DI RUMAH SAKIT BHAYANGKARA PEKANBARU TAHUN 2024 - Candra, Leon; Chairunnissa, Giffa Zira; Widodo, M. Dedi (Journal of Hospital Administration and Management (JHAM), 2024)
Medical records are documents that contain patient identity data, examinations, treatment, procedures and other services that have been provided to patients. Quality and effective medical records require several adequate factors at Bhayangkara Hospital. Management of medical records is still inadequate, indicating obstacles in the level of human resource competency, SOPs and infrastructure. The aim of the research is to determine the management of medical records at Bhayangkara Hospital in 2024. This research uses descriptive research with a qualitative approach. The subjects in this study were 4 people. Data collection techniques use observation, interviews and documentation methods. The results of the research found that the number of human resources in the Medical Records unit was 13 people, not in accordance with the standards for Type C Hospitals. SOPs already existed and were in accordance with the provisions of the Ministry of Health but had not been socialized and posted in the Medical Records room. And the infrastructure already exists but is not adequate, such as shelves for medical record files, lack of computers, scanning machines and trolleys for medical record files. The research concluded that Medical Records Human Resources (HR) were inadequate, Standard Operating Procedures (SOP) were in accordance with the Ministry of Health but had not been socialized and infrastructure was still lacking and inadequate. It is recommended to further improve the quality of Human Resources (HR), improve education and training, for Standard Operating Procedures (SOP) so that SOPs are displayed clearly in the medical record area and increase socialization about these procedures. and optimize and increase the number and quality of infrastructure facilities in the medical records room.